A Study on the Strategic Management Processes of Christian Schools in Thailand - Mazzrillo, Anthony; Mangkang, Pojanee; Phothisuk, Annop (ASEAN Journal of Education, 2024)
This qualitative study aimed to address three objectives related to the strategic management of Christian schools in Thailand: (1) to examine the strategic management processes implemented by these schools, (2) to identify common themes, challenges, and best practices, and (3) to propose guidelines to support effective strategic management in this educational context. Twelve Christian school administrators were selected by purposive sampling based on their leadership roles and familiarity with their schools' strategic management processes, with data collected through an online pre-interview survey and in-depth interviews. Findings revealed that the administrators primarily employed strategic management practices that included regular staff meetings, data analysis, stakeholder feedback, and flexibility in addressing challenges. Spiritual health was supported through daily personal devotions, corporate chapel services, and Bible studies, with a primary emphasis on centering their schools around Jesus Christ. Identified themes included effective communication, partnership-building, adherence to Bible-based morals and ethics, and Bible integration within the curriculum. Challenges reported were hiring the right personnel, financial constraints, communication barriers, managing relationships with diverse stakeholders, and collaborating with individuals from varied backgrounds and belief systems. Best practices highlighted the importance of Christian leaders having a divine calling to work in these schools, engaging in daily personal devotions, and modeling Christian values for teachers, students, and staff. Leaders were also encouraged to align policies with Christian values while being sensitive to non-Christian stakeholders. The study proposes ten guidelines to enhance strategic management processes for Christian schools: (1) Divine Calling and Spiritual Foundation, (2) Biblical Worldview Integration, (3) Sensitivity and Inclusivity, (4) Statement of Faith and Parental Agreement, (5) Hiring Practices, (6) Accountability and Oversight, (7) Cultural Understanding and Adaptation, (8) Addressing Violations, (9) Decision-Making and Boundaries, and (10) Building Positive Partnerships with colleagues and parents.